Safety electrical - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The purpose of this unit is to give trainees a general understanding of basic principles of electricity and electrical safety. At the conclusion of htis unit, trainees will have a basic understanding of various aspects of working safely around electrical equipment.
Keywords: Electrical engineering -- Safety measures; Electrical engineering; Electricity